2017
DOI: 10.1177/0276237417719637
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Accompanying Text on Visual Processing and Hedonic Evaluation of Art

Abstract: This study explores how accompanying text affects the way an individual views and interprets a painting. We randomly assigned participants to view 20 paintings from the classical era with factual information, contextualized background information, or no information displayed next to them. We then recorded their visual gaze using an eye-tracking device and asked them to evaluate the paintings. The results show that how people view a painting and how they evaluate a painting are two distinct cognitive processes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…A possible interpretation would be that the contextualizing information guided participants in their experience, facilitating their search for meaning in the artwork, which could have resulted in less cognitive effort while trying to find a personal meaning and understanding. This is in alignment with results by Lin and Yao (2018), who also found that even though information disrupts visual attention, it makes it easier for participants to effectively process the painting. Taken together, these findings suggest that contextualizing information might facilitate the contemplation and reflection of art, allowing "easier" processing of an artwork.…”
Section: Mediation Effectssupporting
confidence: 89%
See 2 more Smart Citations
“…A possible interpretation would be that the contextualizing information guided participants in their experience, facilitating their search for meaning in the artwork, which could have resulted in less cognitive effort while trying to find a personal meaning and understanding. This is in alignment with results by Lin and Yao (2018), who also found that even though information disrupts visual attention, it makes it easier for participants to effectively process the painting. Taken together, these findings suggest that contextualizing information might facilitate the contemplation and reflection of art, allowing "easier" processing of an artwork.…”
Section: Mediation Effectssupporting
confidence: 89%
“…Also, participants generally liked figurative artworks with title better (Bubić, Sušac, & Palmović, 2017;Lin & Yao, 2018).…”
Section: The Role Of Contextualizing Information In Environmental Artmentioning
confidence: 99%
See 1 more Smart Citation
“…-Increase in the number of fixations associated with abstract paintings is greater for naive viewers than expert viewers (Pihko et al, 2011) and the maximum fixation duration is longer for naive viewers (Locher, Krupinski, & Schaefer, 2015). -Art knowledge and frequency of attendance to art events correlate positively with the number of fixations on paintings but are not related to fixation durations or revisits (Lin & Yao, 2018).…”
mentioning
confidence: 88%
“…194-198 for a review; Crozier and Chapman, 1981, for a review across all art forms). Additional evidence for effects of prior information was also provided by a number of more recent studies on the perception, enjoyment, and evaluation of music (Anglada-Tort & Müllensiefen, 2017;Kroger & Margulis, 2016;Margulis, 2010;Margulis, Kisida, & Greene, 2015;North & Hargreaves, 2005;Vuoskoski & Eerola, 2015;Ziv & Moran, 2006), art works, such as digital reproductions of paintings (Kirk, Skov, Hulme, Christensen, & Zeki, 2009;Lauring et al, 2016;Lin & Yao, 2017), photos (Tousignant & Bodner, 2014), poems (Blohm, Menninghaus, & Schlesewsky, 2017), or live theater performances (Wagner et al, 2015).…”
mentioning
confidence: 95%